Historic development in immigrant novels: the Jewish conflict in Anzia Yezierska's bread givers and Herman Wouk's Majorie Morningstar - Bélinki, Karmela (Nordisk judaistik/Scandinavian Jewish Studies, 1992)
The two novels of this paper, Anzia Yezierska’s Bread Givers and Herman Wouk´s Marjorie Morningstar, represent sequent generations in American Jewish immigrant literature. Bread Givers (1925) is partly an autobiographical novel, the story of an American Jewish immigrant girl in conflict with her traditional role as the servile daughter of a demanding father and the growing impact of American society. Marjorie Morningstar (1955) treats basically the same theme, the clash between tradition and transition, although from the point of view of second generation immigrants. The basic fears of assimilation and loss of identity in the Jewish sense are still there. Both novels also focus on the role of women and particularly the changing role of Jewish women.